A Systematic Review on The Circular Economy Initiatives Through the Sustainability Reporting: A Socio-Cultural Approach (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the last decades, sustainability has been involved in several businesses' policy statements. This study aims to review and summarize the related literature highlighting the relationship between cultural diversity (CD) and sustainability reporting (SR). This article conducts a systematic review of 612 papers in the association between CD and SR. The findings of the review were analyzed using 27 papers as a primary article. Reviewing the past studies shows that the accounting literature is opulent in studies discussed from many viewpoints in SR characteristics. However, studies have not yet provided a clear explanation of the international differences of SR level.[copyright information to be updated in production process]